(untitled) (Revista Venezolana de Salud Pública, 2018)
There are multiple physiopathological causes in which the physical activity is involved to counterattack the risk of disease; therefore it is important that the medical student knows about the physiological effects of exercise, because these aren’t pharmacologist’s measures that improve the quality of life of patients. The objective was to determine the immediate effects of exercise on hemodynamic, methabolic and anthropometric parameters in karate athletes. It was designed a prospective longitudinal descriptive study; the sample was composed of 27 athletes. the mentioned parameters were measured before starting the exercise and after an hour of physical activity. It was found a predominance of males(59,3%), the average age was 16,97 ± 8,0 years old. The average fat percentage was 7,90 ± 6,9. In relation to waist size 40,7% were obese. In terms of body mass index 11.1% were overweight. It showed a significant statistical difference in weight, heart rate, respiratory rate and diastolic blood pressure ((p = 0,0001; p = 0,001; p= 0,001 y p = 0,04 respectively). Even though in blood glucose levels, in systolic blood pressure, and The oxygen saturation were observed differences between the averages before and after exercise, there weren’t statistically significant. It was concluded that exercise has immediate effects on heart and respiratory rate, diastolic blood pressure as well as weight.